2021
DOI: 10.1016/j.stemcr.2021.03.001
|View full text |Cite
|
Sign up to set email alerts
|

One-step Reprogramming of Human Fibroblasts into Oligodendrocyte-like Cells by SOX10, OLIG2, and NKX6.2

Abstract: Summary Limited access to human oligodendrocytes impairs better understanding of oligodendrocyte pathology in myelin diseases. Here, we describe a method to robustly convert human fibroblasts directly into oligodendrocyte-like cells (dc-hiOLs), which allows evaluation of remyelination-promoting compounds and disease modeling. Ectopic expression of SOX10, OLIG2, and NKX6.2 in human fibroblasts results in rapid generation of O4 + cells, which further differentiate into MBP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…This outcome was consistent with previous ndings showing that the single TF SOX10 alone could not directly induce an OL fate in hiPSCs (5,41). Recently, Chanoumidou et al published a rapid protocol for the generation of O4 + cells induced by ectopic expression of TF cocktails, including SOX10, Olig2, and NKX6.2, in human broblasts, which further differentiated into MBP + mature OL-like cells within 16 days (42). TF cocktails show a powerful propensity for inducing OL lineage speci cation.…”
Section: Discussionsupporting
confidence: 90%
“…This outcome was consistent with previous ndings showing that the single TF SOX10 alone could not directly induce an OL fate in hiPSCs (5,41). Recently, Chanoumidou et al published a rapid protocol for the generation of O4 + cells induced by ectopic expression of TF cocktails, including SOX10, Olig2, and NKX6.2, in human broblasts, which further differentiated into MBP + mature OL-like cells within 16 days (42). TF cocktails show a powerful propensity for inducing OL lineage speci cation.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, age-related epigenetic properties are erased during iPSC reprogramming and yield rejuvenated cells. Direct conversion studies on iNs and induced oligodendrocytes, on the other hand, have been shown to generate cells that retain aging phenotypes ( Chanoumidou et al., 2021 ; Mertens et al., 2015 ). Thus, for modeling of sporadic neurodegenerative disorders, in which age is the most significant risk factor, direct conversion constitutes an attractive approach for generation of diseased cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, only miconazole, clobetasol and benztropine did increase the percentage of MBP + mature hiOLs after 21 days in culture, suggesting that species-specific differences could be relevant for drug screening ( Ehrlich et al, 2017 ). Accordingly, benztropine and clemastine enhanced the terminal differentiation and maturation also of hiOLs derived from direct conversion of fibroblast with SON construct, while miconazole showed a milder but still significant effect ( Chanoumidou et al, 2021 ). High-throughput screening (HTS) applied to human iPSC-derived neurons and OLs co-culture also demonstrated enhanced myelination after treatment with miconazole, clobetasol and pranlukast ( Garcia-Leon et al, 2018 ).…”
Section: Applications Of Induced Pluripotent Stem Cells-derived Cells and Cerebral Organoids To Drug Discovery: Advantages And Challengesmentioning
confidence: 99%
“…Finally, another outstanding paper ( Chanoumidou et al, 2021 ) has described a robust and highly reproducible protocol for the direct conversion of human young, adult, and old-aged fibroblasts into OLs by overexpressing the SON construct for 16 days ( Figure 2H ). From 9 days post infection on, directly converted human induced OL-like cells (dc-hiOLs) progressively acquired a branched morphology upon medium enrichment with differentiation factors (including NT3, insulin-like growth factor 1, and dibutyryl cyclic).…”
Section: Models To Study Human Oligodendrocytes In Physiology and Diseasementioning
confidence: 99%